"Is it Going to be Real?" Narrative and Media on a Pandemic - Davis, Mark (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2017)
In this article, I examine the narrative-media nexus as it relates to pandemics. Communications feature in global public health efforts to address the emergence of a pandemic, an event typically marked by the proliferation of news stories. Pandemics are also a perennial subject of film, television, literature and online games and pandemic narratives travel across and blend the genres of science fiction, alien invasion and zombie horror. Underlining this genre-blending, public health communication on pandemics has appropriated the figure of the zombie to encourage interest in preparation for pandemic threats. Drawing on examples from public communications and popular culture in dialogue with interviews and focus groups conducted with health professionals and members of the general public, I advance an account of the transmediated knowledge and meanings of pandemic narrative. I examine how pandemics become objects of knowledge in narrative, the ways in which narrative is appropriated to communicate a pandemic's temporal and affective qualities, and how, in the circumstances of an actual outbreak, publics are invited to consider themselves as the ideal, "alert, but not alarmed" subjects of the pandemic storyworld. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs1701187